Using Audit Committee and Internal Audit Function Inter-Relationships to Drive Up Effectiveness - Razak, Naqiah; Muhamad, Rusnah (Asian Journal of Accounting Perspectives, 2015)
The Audit Committee (AC) has become a common mechanism for ensuring good corporate governance in firms. The interaction between the AC and Internal Audit Function (IAF) is important for the AC in fulfilling its oversight responsibilities. Hence, it is very important that the interaction between the respective roles of the AC and IAF is of good quality. However, little is understood about the quality of the interaction between these two roles. Extant literature suggests that a conclusive theory and/or theories are lacking that can provide an in depth understanding of how the AC and IAF foster a quality working relationship between their respective roles. Hence, we are proposing the relational coordination theory as a framework to enrich the understanding of the interaction between the AC and IAF. This conceptual paper reviews the literature on the AC effectiveness (ACE) and process, and analyses how the interaction quality can be determined using the proposed conceptual model encapsulating this theory.